The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0301-4738.136234
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer and ganglion cell complex thickness in patients with type 2 diabetes mellitus

Abstract: Aim:The aim of the following study is to evaluate the retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness in patients with type 2 diabetes mellitus (DM).Materials and Methods:Average, inferior, and superior values of RNFL and GCC thickness were measured in 123 patients using spectral domain optical coherence tomography. The values of participants with DM were compared to controls. Diabetic patients were collected in Groups 1, 2 and 3. Group 1 = 33 participants who had no diabetic retinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…This suggests that RGC loss, as reflected by GC-IPL thinning which begins before microvascular lesions become apparent, is progressive in subsequent severe forms of DR development. Previous studies by Demir et al 18 and Park et al, 19 using different OCT algorithms to measure different RGC parameters, such as ganglion cell complex thickness, did not demonstrate a significant association of RGC loss with increased DR severity. Although the GC-IPL and the RNFL were measured as a combined thickness, it is still reasonable to expect changes in the OCT parameter, should there be presence of neuronal damage, as loss of ganglion cell bodies will lead to corresponding axonal loss.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This suggests that RGC loss, as reflected by GC-IPL thinning which begins before microvascular lesions become apparent, is progressive in subsequent severe forms of DR development. Previous studies by Demir et al 18 and Park et al, 19 using different OCT algorithms to measure different RGC parameters, such as ganglion cell complex thickness, did not demonstrate a significant association of RGC loss with increased DR severity. Although the GC-IPL and the RNFL were measured as a combined thickness, it is still reasonable to expect changes in the OCT parameter, should there be presence of neuronal damage, as loss of ganglion cell bodies will lead to corresponding axonal loss.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, studies by Demir et al 18 and Park et al, 19 examining RGC loss with increased severity of DR, have found no significant association. 18,19 It is also important to note that previous OCT studies had inadequate attempt to control for the confounding effect of glycemic control, blood pressure, diabetes duration and ocular axial length. In view of these factors, we further evaluate the association of diabetes and DR with RGC loss.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This distinction is of importance to verify the isolated effect of homeostatic disorders due to ESRD and HD on retinal layer volume, as retinal alterations, as a sign of neuronal degeneration have been previously described in patients with T2DM [31][32][33] . For example, a cross-sectional study by Li et al evaluating differences in retinal layer thickness by means of OCT showed a significant thinning of the layers containing parts of the ganglion cells in patients with T2DM even in the absence of early signs of diabetic retinopathy 32 .…”
Section: Discussionmentioning
confidence: 89%
“…Van Dijk et al [25][26][27] reported thinning of inner retinal structures and RGCs in diabetic subjects with no DR or with minimal DR using automated segmentation of SD-OCT scans. Demir et al 30 reported thinning of ganglion cells complex and RNFL in diabetic subjects with various stages of NPDR, but with no statistically significant difference compared with healthy controls. Lopes de Faria et al 31 reported no significant difference in RNFL thickness in subjects with or without DR.…”
Section: Discussionmentioning
confidence: 99%